Consequences of fire and cattle browsing on ground beetles (Coleoptera) in NW Patagonia - Sasal, Yamila (2015)
Understanding the responses of natural communities to disturbances remains a challenging task in ecology. In northwestern Patagonia, the most important disturbances are fire and introduced ungulates. Although these disturbances have been present in this region since late eighteen century, their effects on arthropods diversity have been poorly studied. Here, we examined the short-term response of ground beetles (Coleoptera) to fire (burnt and unburnt) in browsed forests and to cattle browsing (cattle and no cattle) in post-fire forests. We collected ground beetles with pitfall traps and estimated beetle abundance, species richness, assemblage composition, abundance of trophic guilds and beetle characteristic species, and measured some habitat parameters. We found that burnt browsed forest had lower diversity and different assemblage composition than unburnt forest. Beetle abundance, assemblage composition and abundance of trophic guilds were similar in post-fire forests with and without cattle browsing. Conversely, beetle species richness was higher in cattle than in no cattle forests. Fire had a strong negative effect on beetle diversity probably by its effect changing habitat structure. Whereas fire had a homogenizing influence on beetle diversity with and without cattle, at small-spatial scales, browsing of cattle probably generate habitat heterogeneity enhancing beetle richness. The implementation of policies aimed to reduce the risk of fire and to maintain low-moderate cattle pressure appears to be vital to conserve the beetle assemblage in the Patagonian region.